Prevalence of myocarditis, genetic cardiomyopathies and their combinations among patients of the Cardiology Hospital of the V.N. Vinogradov Faculty Therapeutic Clinic of the Sechenov University - D. V. Ruchkin; A. A. Nartova; A. I. Zaitseva; Yu. A. Lutokhina; O. V. Blagova; I. N. Alijeva; N. D. Sarkisova; A. V. Nedostup (Кардиоваскулярная терапия и профилактика)
Aim. To establish the prevalence of myocarditis and primary (genetic) cardiomyopathies (CMP) among patients in a cardiology hospital.Material and methods. Medical records of 671 patients of the cardiology department were analyzed. The diagnosis at admission and at discharge was recorded. The diagnoses were divided into 7 following categories: hypertension, coronary artery disease, heart disease, idiopathic arrhythmias, cardiomyopathy, myocarditis and others. Types of myocarditis and cardiomyopathy, the presence of arrhythmias and heart failure were also recorded.Results. Myocarditis was diagnosed in 194 (28,9%) patients, cardiomyopathy — in 76 (11,3%) patients, combination of cardiomyopathy and myocarditis — in 26 (3,9%) patients. Myocarditis with the development of arrhythmia and heart dilatation prevailed as follows: 47,4 and 41,2%, respectively. The most numerous CMPs were left ventricular noncompaction (n=30), non-inflammatory dilated CMP (n=13), hypertrophic CMP (n=10) and arrhythmogenic CMP of the right ventricle (n=9). In the group with idiopathic arrhythmias, 64,3% of patients were diagnosed with myocarditis, and 19,4% — with cardiomyopathy.Conclusion. The prevalence of non-coronary myocardial diseases among patients in a cardiology hospital is high and amounts to 40,2%. The presence of arrhythmias, heart failure or dilated cardiomyopathy may be a manifestation of non-coronary myocardial diseases, and requires a comprehensive examination aimed, in particular, at ruling out or verifying the diagnosis of myocarditis.